2023
DOI: 10.1111/codi.16589
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pouch failure: A tertiary care inflammatory bowel disease centre experience

Abstract: Aim: Rates of pouch failure after total proctocolectomy with ileal pouch−anal anastomosis (IPAA) range from 5% to 18%. There is little consistency across studies regarding the factors associated with failure, and most include patients who underwent IPAA in the pre-biologic era. Our aim was to analyse a cohort of patients who underwent IPAA in the biologic era at a large-volume inflammatory bowel disease institution to better determine preoperative, perioperative and postoperative factors associated with pouch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We found that 15% of patients with focal inflammation on initial endoscopy subsequently developed diffuse inflammation, suggesting that pouch monitoring for early detection of the endoscopic phenotype is an important component of strategies for maintaining healthy pouch condition. Patients with pouch fistula are known to have poor outcomes [ 6 ]. We identified 7 patients with pouch fistula and the proportion of diffuse inflammation of the pouch body was 71% in this group, suggesting fistulas developed due to chronic inflammation such as pouch with Crohn’s disease-like features [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 15% of patients with focal inflammation on initial endoscopy subsequently developed diffuse inflammation, suggesting that pouch monitoring for early detection of the endoscopic phenotype is an important component of strategies for maintaining healthy pouch condition. Patients with pouch fistula are known to have poor outcomes [ 6 ]. We identified 7 patients with pouch fistula and the proportion of diffuse inflammation of the pouch body was 71% in this group, suggesting fistulas developed due to chronic inflammation such as pouch with Crohn’s disease-like features [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, inflammation of the reservoir can develop, commonly termed “pouchitis.” [ 2 ] Several recent studies have reported a cumulative incidence of acute pouchitis is 30% and approximately 10% to 15% of patients with acute pouchitis develop chronic pouchitis in patients with UC [ 2 - 4 ]. Furthermore, the incidence of pouch failure requiring diverting loop ileostomy (DLI) or pouch excision is reportedly up to 10% and pouch with Crohn’s disease-like features is a significant risk factor of pouch failure [ 2 , 5 , 6 ]. Although the International Ileal Pouch Consortium has established several consensus guidelines for the management of pouchitis [ 7 , 8 ], there remains uncertainty regarding the monitoring, prophylaxis, and pathogenesis of pouchitis in UC.…”
Section: Introductionmentioning
confidence: 99%
“…42 Additional risk factors include preoperative CD, strictures, chronic pouchitis, fistulas, and persistent pouch dysfunction. 42,43 Preoperative biologic use, CLIPI, and prior pouch revision have also been found to be associated with higher failure rates. 43 More recently, CLIPI is being identified as an increasingly frequent cause of pouch failure at high-volume centers.…”
Section: Pouch Failure In Crohn's-like Ileal Pouch Illnessmentioning
confidence: 99%
“…42,43 Preoperative biologic use, CLIPI, and prior pouch revision have also been found to be associated with higher failure rates. 43 More recently, CLIPI is being identified as an increasingly frequent cause of pouch failure at high-volume centers. In fact, pouch failure occurs in up to 60% of pouch patients with CD, especially fistulizing disease with perianal involvement.…”
Section: Pouch Failure In Crohn's-like Ileal Pouch Illnessmentioning
confidence: 99%
“… 7 , 8 Construction of RPC-IPAA in these patients often is painstaking due to multiple postoperative complications and may result in pouch failure range from 5% to 18% when the ultimate diagnosis is CC with significant morbidity. 7 , 9 , 10 Change of diagnosis of IC to UC or CC is also observed in patients with IBD before colectomy, 11 , 12 as is the development of de novo Crohn’s ileitis after surgical intervention. 10 Incorrect diagnosis and treatment course carries potential morbidity from inappropriate and unnecessary surgeries, 8 , 13 and underscores the necessity of research efforts aimed at a more accurate diagnosis of the IBD.…”
Section: Introductionmentioning
confidence: 99%